A method for preparing a super-hydrophilic titanium implant
Patent Information
- Application Number
- CN202611279067.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]然而,ASD处理方法,一方面种植体表面亲水性不足,另一方面容易带来电解质溶液中的化学成分污染,且该污染在纳米层表面上不易清除,从而限制了种植体植入后新生骨的形成
本发明提供的超亲水钛种植体表面的制备方法,首先通过喷砂形成微米级大坑洞,然后通过阳极氧化在微米大坑洞上形成纳米管状结构,进一步酸蚀处理使得种植体表面构建微米级的小坑洞,从而形成梯度微纳复合结构,磷酸和盐酸同时温和清除阳极氧化留下的污染层、氧化膜,与钛反应在表面留下大量Ti-OH;
Smart Images

Figure CN122894548A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of implant technology, specifically relating to a method for preparing a superhydrophilic titanium implant. Background Technology
[0002] Implant restoration is currently recognized by the dental community as the preferred restorative method for patients with missing teeth. The most crucial factor for the success of implant restoration is the osseointegration between the implant and the bone. Currently, it generally takes 3-6 months for osseointegration to occur before the superstructure can be restored. This significantly impacts patients' work and daily life. Promoting early osseointegration, improving the early load-bearing capacity of the implant, and accelerating the superstructure restoration time, thereby shortening the treatment cycle, are current hot topics in clinical research on dental implants. Among these, implant surface treatment is a particularly important technique and a relatively effective and controllable method.
[0003] Titanium is a silvery-gray metal that is easily oxidized in air to form an oxide film of 1.8–17 nm, exhibiting excellent biocompatibility and corrosion resistance, making it widely used in dental implants. The chemical composition, morphology, and surface energy of the titanium surface all affect its biocompatibility and activity. After physical, chemical, and biological modification treatments, the surface morphology, chemical composition, and bioactivity of titanium implants are altered, thereby promoting osseointegration.
[0004] Common surface treatment methods include sandblasting, acid etching, anodizing, hydroxyapatite coating, and plasma treatment. Sandblasting can effectively increase the surface roughness of implants, but because the resulting rough surface morphology is irregular, the surface stress distribution is uneven, and it cannot form three-dimensional cavities, it easily causes contamination of the implant surface. Therefore, it is rarely used alone nowadays. Sandblasting and acid etching treatments create a relatively regular, rounded, and uniformly distributed micron-sized structure on the titanium surface. Acid etching can eliminate the angular structure of sandblasting particles and the titanium surface, while simultaneously forming multi-level cavities, which can compensate for the shortcomings of sandblasting to some extent.
[0005] Compared to sandblasting, anodizing can form a nanolayer on the titanium surface. This nanostructure improves bone integration and enhances the surface texture compared to traditional sandblasting, resulting in stronger bone integration and greater adhesion strength. This promotes new bone formation and improves implant bone integration. Compared to simple sandblasting (RBM) and acid etching (SLA) methods, anodizing (ASD) significantly enhances the new bone formation capacity of the titanium surface, thereby improving the fixation strength of titanium in bone.
[0006] However, the ASD treatment method has two drawbacks: firstly, the implant surface lacks sufficient hydrophilicity, and secondly, it is prone to contamination by chemical components in the electrolyte solution. This contamination is difficult to remove from the nanolayer surface, thus limiting the formation of new bone after implantation. Summary of the Invention
[0007] To address the shortcomings of existing technologies, a method for preparing a superhydrophilic titanium implant surface is provided.
[0008] The objective of this invention is achieved through the following technical solution: This invention provides a method for preparing the surface of a superhydrophilic titanium implant, comprising, Titanium material is mechanically processed into implants. After sandblasting the surface of the implants, anodizing is performed using the implant surface as the anode to obtain titanium implant surface I. Titanium implant surface I was immersed in a mixed acid solution of phosphoric acid and hydrochloric acid for acid etching treatment to obtain titanium implant surface II; The titanium implant surface II was ultrasonically vacuum cleaned to obtain the titanium implant surface III; Vacuum plasma treatment was performed on titanium implant surface III to obtain a superhydrophilic titanium implant surface; The ultrasonic vacuum cleaning process includes first ultrasonic vacuum cleaning with an alkaline compound solution, and then ultrasonic vacuum cleaning with pure water.
[0009] In some specific embodiments of the present invention, the sandblasting medium is selected from one of hydroxyapatite, calcium phosphate, alumina, silicon dioxide, and titanium dioxide.
[0010] In some specific embodiments of the present invention, the sandblasting medium is calcium phosphate, and the particle size of the calcium phosphate is 250~500 μm.
[0011] In some specific embodiments of the present invention, the electrolyte for the anodic oxidation treatment is selected from one or more of hydrofluoric acid, phosphoric acid, sulfuric acid, and ammonium dihydrogen phosphate; in the anodic oxidation treatment, the DC power supply voltage is controlled at 100~200V, and the oxidation time is controlled at 1~5 min.
[0012] In some specific embodiments of the present invention, the mixed acid solution is obtained by mixing concentrated hydrochloric acid, concentrated phosphoric acid, and water in a volume ratio of 2:1:1.
[0013] In some specific embodiments of the present invention, the acid etching temperature is 50~100℃ and the acid etching time is 1h.
[0014] In some specific embodiments of the present invention, the alkaline compound is selected from one or more of sodium hydroxide, calcium hydroxide, sodium carbonate, and sodium silicate.
[0015] In some specific embodiments of the present invention, the ultrasonic vacuum cleaning time of the alkaline compound solution is 10-20 min, and the ultrasonic vacuum cleaning time of the pure water is 30-40 min; the ultrasonic vacuum cleaning temperature is 30-50℃, the power is 0.6 kW, and the frequency is 28-40 kHz.
[0016] In some specific embodiments of the present invention, the gas used for vacuum plasma treatment is a mixture of argon and oxygen, wherein the volume ratio of argon to oxygen is 95:5.
[0017] In some specific embodiments of the present invention, the plasma treatment time is 1~3 min, the vacuum degree is 5~30 Pa, the radio frequency is 10~15 MHz, and the temperature is controlled at 20~50℃.
[0018] The beneficial effects achieved by this invention are as follows: The method for preparing the surface of a superhydrophilic titanium implant provided by the present invention firstly forms micron-sized large pits by sandblasting, then forms nanotube-like structures on the micron-sized large pits by anodizing, and further acid etching treatment makes the implant surface construct micron-sized small pits, thereby forming a gradient micro-nano composite structure. Phosphoric acid and hydrochloric acid simultaneously and gently remove the contamination layer and oxide film left by anodizing, and react with titanium to leave a large amount of Ti-OH on the surface. Building upon this foundation, acidic substances within the micro / nano structure are removed through vacuum ultrasonic cleaning, followed by vacuum plasma treatment. This effectively removes other contaminants from the implant surface and introduces oxygen-containing polar functional groups, achieving superhydrophilicity on the implant surface without disrupting the original micro / nano composite structure morphology. Through the synergistic effect of the micro / nano composite structure and superhydrophilicity, titanium implants not only possess excellent anchoring force but also a higher osseointegration area, enabling effective osseointegration after implantation. Attached Figure Description
[0019] To more clearly illustrate the technical solution of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a schematic diagram of the anodizing surface treatment in Embodiment 1 of the present invention.
[0021] Figure 2 This is a schematic diagram of the vacuum plasma treatment device in Embodiment 1 of the present invention.
[0022] Figure 3These are morphological images of the titanium implant surface after anodizing in Example 1 of the present invention and the titanium implant surfaces finally obtained in Comparative Examples 1 to 3 at different magnifications (×1000, ×5000).
[0023] Figure 4 This is a comparison diagram of the cell adhesion on the surface of the titanium implants finally prepared in Example 1 and Comparative Examples 1 to 3 of the present invention.
[0024] Figure 5 These are morphological images of the titanium implants obtained in Example 1 and Comparative Examples 1 to 3 of the present invention after culturing osteoid cells on the surface for 24 hours, at different magnifications (×500, ×2000).
[0025] Figure 6 The images show histological examination and analysis of the titanium implants finally prepared in Example 1 and Comparative Examples 1 to 3 of this invention 8 weeks after the implantation surgery.
[0026] Figure 7 These are magnified images of the surface of the titanium implant finally obtained in Example 1 of the present invention at different magnifications.
[0027] Figure 8 These are magnified images of the surface of the titanium implant finally obtained in Comparative Example 4 of this invention at different magnifications.
[0028] Figure 9 The figures show the hydrophilicity test results of the titanium implant surfaces finally obtained in Example 1 and Comparative Example 4 of this invention. Detailed Implementation
[0029] The present invention will be further described in detail below with reference to specific embodiments. The following embodiments are not intended to limit the present invention, but only to illustrate the present invention. Unless otherwise specified, the experimental methods used in the following embodiments are generally performed under conventional conditions. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.
[0030] The concentrated hydrochloric acid used in this invention has a concentration of 36%–38% and a density of approximately 1.18 g / mL. The concentrated phosphoric acid has a concentration of 85% and a density of approximately 1.69 g / mL. The hydrofluoric acid has a concentration of 40% and a density of approximately 1.13 g / cm³. 3 The nitric acid concentration is 68%, and the density is approximately 1.39 g / cm³. 3 The sulfuric acid concentration is 98%, and its density is approximately 1.84 g / cm³. 3 .
[0031] The cell adhesion experiment method in this invention is as follows: MG-63 cells are cultured on each Ti surface for 3 hours using crystal violet staining analysis.
[0032] In this invention, the contact angle test is performed using the seat drop method at room temperature (25±2℃) and relative humidity of 50±5%, using 2μL of deionized water, and at least 5 different locations are measured for each sample and the average value is taken.
[0033] Example 1 This embodiment provides a method for preparing the surface of a superhydrophilic titanium implant, specifically as follows: (1) Sandblasting and anodizing: TA4G titanium material was machined into implants, and calcium phosphate particles with a particle size of 350 μm were sprayed at a pressure of 0.8 MPa for 5s with a sandblasting distance of 10 cm. Then, an aqueous solution with a final concentration of 5% sulfuric acid and a final concentration of 3% phosphoric acid was used as the electrolyte. The surface of the titanium implant was used as the anode and metal platinum was used as the cathode. After assembly, the implants were reacted at a voltage of 180 V for 3 min to obtain the surface I of the titanium implant. (2) Acid etching: The titanium implant surface I obtained in step (1) is immersed in a mixed acid solution and reacted at 80°C for 1 hour. After washing, the residual acid solution on the implant surface is removed to obtain titanium implant surface II. The mixed acid solution is obtained by mixing concentrated hydrochloric acid, concentrated phosphoric acid and water in a volume ratio of 2:1:1. (3) Ultrasonic vacuum cleaning: The titanium implant surface II obtained in step (2) is ultrasonically vacuum cleaned for 20 min with 0.05M sodium hydroxide aqueous solution, then ultrasonically vacuum cleaned with pure water for 30 min, dried with hot air for 10 min, and vacuum dried for 10 min to obtain titanium implant surface III. The ultrasonic vacuum cleaning temperature is 30℃, the ultrasonic power is 0.6 kW, and the ultrasonic frequency is 28KHz. (4) Vacuum plasma treatment: The titanium implant surface III obtained in step (3) is subjected to plasma treatment with Ar / O2 mixed gas with a volume ratio of 95:5. The plasma treatment vacuum degree is 5 Pa, the frequency is 13.56 MHz, the treatment time is 3 min, and the temperature is controlled at 50℃, thus obtaining the superhydrophilic titanium implant surface of this embodiment.
[0034] A schematic diagram of the anodizing surface treatment in Example 1 is shown below. Figure 1 As shown, the titanium implant serves as the anode, while the platinum rod serves as the cathode. Among them, 1-high-power pulsed DC voltage source, 2-substrate (anode), 3-counter electrode, 4-cooling system, 5-magnetic stir bar, 6-insulating electrolyte tank, 7-fume hood.
[0035] The schematic diagram of the vacuum plasma treatment instrument in Example 1 is as follows: Figure 2 As shown.
[0036] Example 2 This embodiment provides a method for preparing the surface of a superhydrophilic titanium implant, specifically as follows: (1) Sandblasting and anodizing: TA4G titanium material was machined into implants, and calcium phosphate particles with a particle size of 250 μm were sprayed at a pressure of 0.8 MPa for 5s with a sandblasting distance of 10 cm. Then, an aqueous solution with a final concentration of 5% sulfuric acid and a final concentration of 3% phosphoric acid was used as the electrolyte. The surface of the titanium implant was used as the anode and metal platinum was used as the cathode. After assembly, the implants were reacted at a voltage of 100 V for 5 min to obtain the surface I of the titanium implant. (2) Acid etching: The titanium implant surface I obtained in step (1) is immersed in a mixed acid solution and reacted at 50°C for 1 hour. After washing, the residual acid solution on the implant surface is removed to obtain titanium implant surface II. The mixed acid solution is obtained by mixing concentrated hydrochloric acid, concentrated phosphoric acid and water in a volume ratio of 2:1:1. (3) Ultrasonic vacuum cleaning: The titanium implant surface II obtained in step (2) is ultrasonically vacuum cleaned for 10 min with 0.05M sodium hydroxide aqueous solution, then ultrasonically vacuum cleaned with pure water for 30 min, dried with hot air for 10 min, and vacuum dried for 10 min to obtain titanium implant surface III. The ultrasonic vacuum cleaning temperature is 50℃, the ultrasonic power is 0.6 kW, and the ultrasonic frequency is 40KHz. (4) Vacuum plasma treatment: The titanium implant surface III obtained in step (3) is subjected to plasma treatment with Ar / O2 mixed gas with a volume ratio of 95:5. The plasma treatment vacuum degree is 20 Pa, the frequency is 15 MHz, the treatment time is 1 min, and the temperature is controlled at 20℃, thus obtaining the superhydrophilic titanium implant surface of this embodiment.
[0037] Example 3 This embodiment provides a method for preparing the surface of a superhydrophilic titanium implant, specifically as follows: (1) Sandblasting and anodizing: TA4G titanium material was machined into implants, and calcium phosphate particles with a particle size of 500 μm were sprayed at a pressure of 0.8 MPa for 5s with a sandblasting distance of 10 cm. Then, an aqueous solution with a final concentration of 5% sulfuric acid and a final concentration of 3% phosphoric acid was used as the electrolyte. The surface of the titanium implant was used as the anode and metal platinum was used as the cathode. After assembly, the reaction was carried out at a voltage of 200 V for 1 min to obtain the surface I of the titanium implant. (2) Acid etching: The titanium implant surface I obtained in step (1) is immersed in a mixed acid solution and reacted at 100°C for 1 hour. The residual acid solution on the implant surface is removed by washing to obtain titanium implant surface II. The mixed acid solution is obtained by mixing concentrated hydrochloric acid, concentrated phosphoric acid and water in a volume ratio of 2:1:1. (3) Ultrasonic vacuum cleaning: The titanium implant surface II obtained in step (2) is ultrasonically vacuum cleaned for 20 min with 0.05M sodium hydroxide aqueous solution, then ultrasonically vacuum cleaned with pure water for 40 min, hot air dried for 10 min, and vacuum dried for 10 min to obtain titanium implant surface III. The ultrasonic vacuum cleaning temperature is 30℃, the ultrasonic power is 0.6 kW, and the ultrasonic frequency is 28KHz. (4) Vacuum plasma treatment: The titanium implant surface III obtained in step (3) is subjected to plasma treatment with Ar / O2 mixed gas with a volume ratio of 95:5. The plasma treatment vacuum degree is 30 Pa, the frequency is 10 MHz, the treatment time is 3 min, and the temperature is controlled at 50℃, thus obtaining the superhydrophilic titanium implant surface of this embodiment.
[0038] Example 4 The difference between this embodiment and embodiment 1 is that only the sandblasting particles in step (1) are changed to alumina, while the rest of the preparation process is the same as in embodiment 1, resulting in the titanium implant surface of this embodiment.
[0039] Example 5 The difference between this embodiment and embodiment 1 is that only the sandblasting particles in step (1) are changed to titanium oxide, while the rest of the preparation process is the same as in embodiment 1, resulting in the titanium implant surface of this embodiment.
[0040] Comparative Example 1 This comparative example provides a method for preparing the surface of a titanium implant, which involves mechanically processing TA4G titanium material to obtain the surface of the titanium implant of this comparative example.
[0041] Comparative Example 2 This comparative example provides a method for preparing the surface of a titanium implant, which only involves sandblasting and acid etching, specifically: TA4G titanium material was machined into implants. Calcium phosphate particles with a diameter of 350 μm were sprayed onto the surface of the implants at a pressure of 0.8 MPa for 5 seconds at a spraying distance of 10 cm. The implants were then immersed in a mixed acid solution and reacted at 80°C for 1 hour. The residual acid solution on the implant surface was removed by washing. The mixed acid solution was obtained by mixing concentrated hydrochloric acid, concentrated phosphoric acid, and water in a volume ratio of 2:1:1, thus obtaining the titanium implant surface of this comparative example.
[0042] Comparative Example 3 This comparative example provides a method for preparing the surface of a titanium implant, which involves only anodizing, specifically: TA4G titanium material was machined into titanium implants. An aqueous solution with a final concentration of 5% sulfuric acid and 3% phosphoric acid was used as the electrolyte. The surface of the titanium implant was used as the anode and platinum metal was used as the cathode. After assembly, the implants were reacted at 180 V for 3 min to obtain the titanium implant surface of this comparative example.
[0043] The contact angles of the titanium implant surfaces prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1.
[0044] Table 1 Contact angle of titanium implant surface
[0045] The morphology images of the titanium implant surface after anodizing in Example 1 and the final titanium implant surfaces obtained in Comparative Examples 1 to 3 at different magnifications (×1000, ×5000) are shown below. Figure 3 As shown in the figures, (a) and (e) are surface morphology images of the titanium implant in Comparative Example 1, (b) and (f) are surface morphology images of the titanium implant in Comparative Example 2, (c) and (g) are surface morphology images of the titanium implant in Comparative Example 3, and (d) and (h) are surface morphology images of the titanium implant after anodizing in Example 1. In Example 1, the surface I of the titanium implant contains nanotube structures with a diameter of approximately 40-100 nm. The nanotubes are closely arranged, with only a few nanotubes exhibiting fusion.
[0046] The cell adhesion on the surface of the titanium implants finally prepared in Example 1, Comparative Examples 1 to 3 was tested. p<0.05, p<0.01), the results are as follows Figure 4 As shown. From Figure 4 As can be seen, the cell adhesion amounts on the surfaces of Comparative Example 2, Comparative Example 3, and Example 1 were 2.4 times, 1.53 times, and 3.18 times that of the surface of Comparative Example 1, respectively. Therefore, Example 1 exhibited the highest cell adhesion.
[0047] Morphological images of osteoid cells cultured on the surface of the titanium implants finally prepared in Examples 1, 1, and 3 for 24 hours at different magnifications (×500, ×2000), as shown below. Figure 5 As shown. (a) and (e) are surface morphology images of the titanium implant obtained in Comparative Example 1; (b) and (f) are surface morphology images of the titanium implant obtained in Comparative Example 2; (c) and (g) are surface morphology images of the titanium implant obtained in Comparative Example 3; and (d) and (h) are surface morphology images of the titanium implant obtained in Example 1. Figure 5 As can be seen from (g) to (h), numerous filamentous pseudopodia extending in all directions appeared on the surface of the titanium implants in Comparative Example 3 and Example 1.
[0048] The surface roughness S of the titanium implants prepared in Example 1 and Comparative Examples 1-3 was tested. a S q and R t The results are shown in Table 2.
[0049] Table 2 Surface roughness of titanium implants
[0050] As can be seen from Table 2, S in Comparative Example 1 a With a thickness of only 0.08 μm and a nearly smooth surface, compared to the S in Comparative Example 3... a The surface roughness is 0.52 μm, with only a slight improvement, while the S-value of the surfaces in Example 1 and Comparative Example 2 is significantly higher. a The surface roughness reached as high as 1.45 μm and 1.68 μm respectively, showing a significant increase compared to the machined surface. This indicates that sandblasting and acid etching created numerous micron-sized pits. Notably, the Sa value of Example 1 was lower than that of Comparative Example 2, and the maximum peak-to-valley height R... t The thickness decreased significantly from 16.99 μm to 13.76 μm, indicating that after sandblasting and anodizing to generate a relatively uniform oxide film with nanopores on the titanium surface, the subsequent mixed acid etching dissolved the nanotube walls, weakened the sharp protrusions, and filled the micron-sized pits. This helps to reduce stress cutting of the surrounding soft tissue during implantation and improve the bonding strength between the oxide film and the substrate.
[0051] Comparing Example 1 and Comparative Examples 2-3 in Table 2, it can be seen that the anodized S a Although the surface roughness is low, only 0.52 μm, it contains nanoscale pores, and the surface roughness S obtained by sandblasting and acid etching is... a While advanced, it lacks a fine nanoscale structure. In contrast, Example 1 constructs a micron-scale large pit framework through sandblasting and a micron-scale small pit framework through acid etching. The pre-existing anodized nanotubes are not completely eliminated during the subsequent acid etching but instead adhere to the micron-scale small pit framework, forming a composite stepped structure of micron-scale pits and nanotubes of different sizes.
[0052] Eight weeks after the implantation of the titanium implants finally prepared in Example 1 and Comparative Examples 1 to 3, histological examination and analysis were performed. The results are as follows: Figure 6 As shown, Group A contains panoramic views of implant sections, (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Comparative Example 3, and (d) is Example 1. The middle image of each figure is a titanium implant (threaded dental implant) magnified at 12.5x. The threaded area marked by the red box is the target area for observing osseointegration. The left and right sides are preview images of the red-boxed area magnified at 40x. Group B is a magnified image of the threaded area corresponding to the red-boxed area in Group A at 100x. From Figure 6Group A (a) to (d) shows that the number of newly formed bone trabeculae gradually increased and their arrangement became denser, the proportion of the medullary cavity decreased, and the osteogenic capacity around the implant improved. From Figure 6 As can be seen from Group B, (a) there are more bone gaps and sparse bone trabeculae, while (d) the bone tissue is dense and there is a significant increase in mineralized bone around the implant threads.
[0053] according to Figure 6 Eight weeks after the implantation surgery of the titanium implants prepared in Examples 1 and Comparative Examples 1-3, the bone-to-implant contact ratio (BIC) in the uppermost second and third threads, and the bone mineral density (ITBD) in the uppermost second and third threads were calculated. The results are shown in Table 3. p<0.05, p<0.01.
[0054] Table 3 BIC and ITBD of titanium implants
[0055] Comparing Example 1 with Comparative Examples 1 to 3 in Table 3, it can be seen that the BIC values of implants treated with only sandblasting, acid etching, and anodizing are similar, approximately 58% to 59%. However, Example 1 has the highest BIC value. While retaining the strong anchoring force of the nanotubes, it undergoes further acid etching. The mixed acid solution of phosphoric acid and hydrochloric acid effectively removes the contamination layer and part of the dense oxide film left by anodizing. At the same time, it reacts with titanium to leave a large amount of Ti-OH on the surface. After removing impurities in the micro-nano structure by ultrasonic vacuum cleaning, plasma treatment introduces more polar groups to the surface of the nanotubes and further increases the Ti-OH density. This greatly promotes the chemical bonding of the bone-bonding interface. Due to the synergistic effect of the micro-nano structure framework and the superhydrophilicity of the nanoscale surface, the BIC value of the titanium implant is increased to 74.20%.
[0056] Regarding the ITBD value, Comparative Example 3, which only underwent anodizing, was slightly higher than Example 1, and both were much higher than the implant surface that only underwent sandblasting and acid etching. This is because the physical interlocking resistance provided by the titanium dioxide nanotube array generated by anodizing, which penetrates deep into the bone ingrowth interface, is much greater than that of the micron-sized sandblasting pits.
[0057] In summary, the implant surface prepared in Example 1 not only has good anchoring force but also has a higher osseointegration area, enabling effective osseointegration after implantation.
[0058] Comparative Example 4 The difference between this comparative example and Example 1 is that steps (3) and (4) are not performed, while the rest of the preparation process is the same as in Example 1, resulting in the titanium implant surface of this comparative example.
[0059] The morphology images of the titanium implant surface obtained in Example 1 at different magnifications are shown below. Figure 7 As shown, (a) is ×300, (b) is ×1000, (c) is ×2000, and (d) is ×5000.
[0060] Comparative Example 4 shows the morphology of the final titanium implant surface at different magnifications, as shown in the following figures. Figure 8 As shown, (a) is ×300, (b) is ×1000, (c) is ×2000, and (d) is ×5000.
[0061] contrast Figure 7 and Figure 8 It can be seen that the vacuum plasma superhydrophilic treatment after ultrasonic vacuum cleaning does not affect the surface micro-nano composite structure morphology obtained by sandblasting, anodizing, and acid etching.
[0062] The surface hydrophilicity test results of the titanium implants prepared in Example 1 and Comparative Example 4 are as follows: Figure 9 As shown in the figure, (a) and (b) represent the surface hydrophilicity of Comparative Example 4, and (c) and (d) represent the surface hydrophilicity of Example 1. It can be seen from the figure that the surfaces obtained by sandblasting, anodizing, and acid etching are weakly hydrophilic because the residual acid and impurities inside the nanotubes are difficult to remove through conventional rinsing. However, ultrasonic vacuum cleaning effectively removes impurities from the nanotubes, and plasma treatment makes it easier to introduce polar groups onto the nanotube surface, thus achieving superhydrophilicity.
[0063] Comparative Example 5 The difference between this comparative example and Example 1 is that only the particle size of the sandblasting calcium phosphate particles in step (1) is adjusted to 150 μm, while the rest of the preparation process is the same as in Example 1, resulting in the titanium implant surface of this comparative example.
[0064] Comparative Example 6 The difference between this comparative example and Example 1 is that only the particle size of the calcium phosphate particles in step (1) is adjusted to 600 μm, while the rest of the preparation process is the same as in Example 1, resulting in the titanium implant surface of this comparative example.
[0065] Comparative Example 7 The difference between this comparative example and Example 1 is that step (3) ultrasonic vacuum cleaning is not performed, and step (4) vacuum plasma treatment is performed directly. The rest of the preparation process is the same as that of Example 1, and the titanium implant surface of this comparative example is obtained.
[0066] Comparative Example 8 The difference between this comparative example and Example 1 is that only the mixed acid solution in step (2) is adjusted to hydrofluoric acid and nitric acid, while the rest of the preparation process is the same as in Example 1, resulting in the titanium implant surface of this comparative example.
[0067] Comparative Example 9 The difference between this comparative example and Example 1 is that only the mixed acid solution in step (2) is changed to sulfuric acid and phosphoric acid, while the rest of the preparation process is the same as in Example 1, and the titanium implant surface of this comparative example is obtained.
[0068] Comparative Example 10 The difference between this comparative example and Example 1 is that only the mixed gas in step (4) is adjusted to be directly compressed air. The rest of the preparation process is the same as that in Example 1, and the titanium implant surface of this comparative example is obtained.
[0069] Comparative Example 11 The difference between this comparative example and Example 1 is that sandblasting and acid etching are performed first, followed by anodizing. All other preparation processes are the same as in Example 1, specifically: (1) Sandblasting and acid etching: TA4G titanium material is mechanically processed into implants. Calcium phosphate particles with a particle size of 350 μm are sprayed onto the surface of the implant at a pressure of 0.8 MPa for 5 s and a sandblasting distance of 10 cm. The implant is then immersed in a mixed acid solution and reacted at 80°C for 1 h. The residual acid solution on the surface of the implant is removed by washing to obtain titanium implant surface I. The mixed acid solution is obtained by mixing concentrated hydrochloric acid, concentrated phosphoric acid and water in a volume ratio of 2:1:1. (2) Anodizing: Using an aqueous solution with a final concentration of 5% sulfuric acid and a final concentration of 3% phosphoric acid as the electrolyte, the titanium implant surface I obtained in step (1) is used as the anode and metal platinum is used as the cathode. After assembly, the reaction is carried out at 180 V for 3 min to obtain titanium implant surface II. (3) Ultrasonic vacuum cleaning: The titanium implant surface II obtained in step (2) is ultrasonically vacuum cleaned for 20 min with 0.05M sodium hydroxide aqueous solution, then ultrasonically vacuum cleaned with pure water for 30 min, dried with hot air for 10 min, and vacuum dried for 10 min to obtain titanium implant surface III. The ultrasonic vacuum cleaning temperature is 30℃, the ultrasonic power is 0.6 kW, and the ultrasonic frequency is 28KHz. (4) Vacuum plasma treatment: The titanium implant surface III obtained in step (3) was subjected to plasma treatment with Ar / O2 mixed gas with a volume ratio of 95:5. The plasma treatment vacuum degree was 5 Pa, the frequency was 13.56 MHz, the treatment time was 3 min, and the temperature was controlled at 50℃, thus obtaining the superhydrophilic titanium implant surface of this comparative example.
[0070] The contact angles of the titanium implant surfaces prepared in Comparative Examples 4 to 11 were tested, and the results are shown in Table 4.
[0071] Table 4 Contact angle of titanium implant surface
[0072] Comparing Example 1 and Comparative Example 4 in Table 4, it can be seen that the surface obtained by sandblasting, anodizing, and acid etching alone, although having a micro-nano composite structure, exhibits weak hydrophilicity due to the presence of contaminants and the absence of functional groups.
[0073] Comparing Example 1 and Comparative Examples 5-6 in Table 4, it can be seen that when the calcium phosphate particles are too small, the resulting micron-sized pits are shallow and have low density. Although plasma treatment can provide hydrophilicity, the micron-sized pores are insufficient, and the contact angle increases significantly. When the calcium phosphate particles are too large, excessively large and deep pits will form on the surface after sandblasting, and even micro-cracks and sharp burrs will appear. This structure will trap air in the micro-pits, forming a solid-gas-liquid composite interface, which hinders the complete spread of droplets. Even after plasma treatment, the contact angle remains high.
[0074] Comparing Example 1 and Comparative Example 7 in Table 4, it can be seen that the contact angle of the implant surface increases. Due to the blockage of nanotubes by anodic oxide contaminants, most of the plasma energy is consumed in bombarding the contaminants, and functional groups cannot be effectively grafted, so the surface hydrophilicity cannot be improved.
[0075] Comparing Example 1 and Comparative Examples 8-9 in Table 4, it can be seen that the mixed acid system of acid etching treatment has a significant impact on the hydrophilicity of the implant surface. When using hydrofluoric acid, HF reacts with the titanium surface during the acid etching process, F... - Ions are chemically adsorbed onto the titanium surface to form Ti-F bonds, occupying active sites and inhibiting the grafting of -OH during subsequent plasma treatment, resulting in implants with lower surface hydrophilicity. In contrast, Comparative Example 9 uses sulfuric acid and SO4. 2- The stable passivation layer only forms shallow pits, and the roughness is insufficient, resulting in low hydrophilicity of the implant surface.
[0076] In Comparative Example 10 in Table 4, the large amount of nitrogen plasma in the air could not completely remove pollutants deep in the nanopores. The residue blocked the grafting sites of subsequent functional groups, and the amine groups generated by the nitridation reaction with the titanium surface were relatively weak, resulting in a decrease in the grafting density of the highly hydrophilic -OH groups on the planting surface, thus failing to achieve superhydrophilicity.
[0077] Comparing Example 1 and Comparative Example 11 in Table 4, it can be seen that the surface hydrophilicity is significantly reduced after sandblasting, acid etching, and then anodizing. In Example 1, sandblasting, anodizing, and then acid etching retained a large number of Ti-OH hydrophilic groups on the surface while removing organic contaminants and forming a more unobstructed stepped micro-nano composite structure, providing a superior activation substrate for subsequent plasma treatment. In contrast, after anodizing in Comparative Example 11, the surface was covered with a dense oxide top layer, and the adsorbed electrolyte anions, sulfate and phosphate, were difficult to remove even after plasma treatment.
[0078] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing the surface of a superhydrophilic titanium implant, characterized in that: include, Titanium material is mechanically processed into implants. After sandblasting the surface of the implants, anodizing is performed using the implant surface as the anode to obtain titanium implant surface I. Titanium implant surface I was immersed in a mixed acid solution of phosphoric acid and hydrochloric acid for acid etching treatment to obtain titanium implant surface II; The titanium implant surface II was ultrasonically vacuum cleaned to obtain the titanium implant surface III; Vacuum plasma treatment was performed on titanium implant surface III to obtain a superhydrophilic titanium implant surface; The ultrasonic vacuum cleaning process includes first ultrasonic vacuum cleaning with an alkaline compound solution, and then ultrasonic vacuum cleaning with pure water.
2. The method for preparing the surface of the superhydrophilic titanium implant according to claim 1, characterized in that: The blasting medium is selected from one of hydroxyapatite, calcium phosphate, alumina, silicon dioxide, and titanium dioxide.
3. The method for preparing the surface of the superhydrophilic titanium implant according to claim 2, characterized in that: The blasting medium is calcium phosphate, and the particle size of the calcium phosphate is 250~500 μm.
4. The method for preparing the surface of the superhydrophilic titanium implant according to claim 1, characterized in that: The electrolyte for the anodic oxidation treatment is selected from one or more of hydrofluoric acid, phosphoric acid, sulfuric acid, and ammonium dihydrogen phosphate; in the anodic oxidation treatment, the DC power supply voltage is controlled at 100~200V, and the oxidation time is controlled at 1~5 min.
5. The method for preparing the surface of the superhydrophilic titanium implant according to any one of claims 1 to 4, characterized in that: The mixed acid solution is obtained by mixing concentrated hydrochloric acid, concentrated phosphoric acid, and water in a volume ratio of 2:1:
1.
6. The method for preparing the surface of the superhydrophilic titanium implant according to claim 5, characterized in that: The acid etching temperature is 50~100℃, and the acid etching time is 1 h.
7. The method for preparing the surface of the superhydrophilic titanium implant according to claim 1, characterized in that: The alkaline compound is selected from one or more of sodium hydroxide, calcium hydroxide, sodium carbonate, and sodium silicate.
8. The method for preparing the surface of the superhydrophilic titanium implant according to claim 7, characterized in that: The ultrasonic vacuum cleaning time for the alkaline compound solution is 10-20 min, and the ultrasonic vacuum cleaning time for the pure water is 30-40 min; the ultrasonic vacuum cleaning temperature is 30-50℃, the power is 0.6 kW, and the frequency is 28-40 kHz.
9. The method for preparing the surface of the superhydrophilic titanium implant according to claim 1, characterized in that: The gas used in the vacuum plasma treatment is a mixture of argon and oxygen, with a volume ratio of argon to oxygen of 95:
5.
10. The method for preparing the surface of the superhydrophilic titanium implant according to claim 9, characterized in that: The plasma treatment time is 1~3 min, the vacuum degree is 5~30 Pa, the radio frequency is 10~15 MHz, and the temperature is controlled at 20~50℃.